The Effect of Fertilization on Plant and Agricultural Traits of Chickpeas - İPEKEŞEN, Sibel and BİÇER, B.Tuba (ISPEC Journal of Agricultural Sciences, 2021)
In this research, the effects of cattle, small cattle manure, solid worm manure and NP on some plant and agricultural traits on Gökçe, Arda, Yerli chickpea (Cicer arietinum L.) varieties were investigated. The trial were arranged according to randomized plots in split plots design with three replications for harvested for full bloom, pod setting and full maturity periods. Fertilizer applications are performed with sowing. Observations were taken for plant height, root length, nodule dry weight, leaf area, number of leaves per plant, leaf dry weight in full blooming and pod setting periods. In full maturity period, plant height, number of pods and seed per plant and seed yield per plant were measured. The effects of fertilizer applications were found significant for investigated traits in all developmental periods. NP fertilization in full flowering positively affected plant height, leaf area, number of leaves and leaf dry weight per plant. Small cattle manure was affected on root length, leaf area and dry leaf weight in the pod setting period. The dry weight of the nodule was higher in the control group during the full flowering period, but small cattle application very important on dry weight of the nodule during the pod setting period. Nodule formation never occurred in NP application. The small cattle manure were positively affect for number of pods, the number of seeds per plant and the seed yield per plant in the full maturity period. It is predicted that organic fertilizers can be given as an alternative to conventional agricultural practices depending on the positive response of the varieties to organic fertilizers among the applications.